Manajemen Likuiditas Dan Struktur Modal Terhadap Profitabilitas PT Unilever - Septiana Mar'atus Sholikhah; Kasmi (Universitas Muhammadiyah Metro, 2025)
The goal of this study was to discover parameters determining profitability. PT Unilever Tbk was sampled utilizing a partial test data collection methodology and multiple linear regression analysis. The findings demonstrated that profitability was not significantly impacted by the liquidity ratio. In the meantime, there was a notable adverse impact on the capital structure ratio. One of the recommendations for Unilever is to sustain debt management through effective liquidity management. Additionally, keeping debt and equity in balance is essential to avoiding bankruptcy.